Biomechanical analysis of mandibular defect reconstruction based on a new base-fixation system. Issue 14 (26th October 2022) - Cui, Haipo; Gao, Liping; Han, Jing; Liu, Jiannan
Abstract: Buccal titanium plate fixation is a common method for repairing mandibular defects. However, the method presents certain problems: the requirement of a large volume of titanium plate, a large number of fixation screws, a lengthy duration of the surgical operation, and exposure of the fixation plate which easily causes wound infection. In this study, a new base-fixation system was designed. Mandibular reconstruction was performed using the three-dimensional reconstruction package Mimics. In order to compare the newly designed base-fixation system and the common buccal-fixation system, the stress distributions and the displacement distributions of the whole model under two loading conditions were studied, based on the finite element analysis package ANSYS. The safety of the base-fixation titanium plate was evaluated. The results showed that although the maximum stress of the base-fixation titanium plate was higher than that of the buccal-fixation titanium plate, it was still less than the yield strength of titanium. Therefore, under the condition of applying 300 N of vertical occlusal loading, the base-fixation titanium plate displayed superior fixation ability without permanent deformation (and concomitant fixation failure). The results of the fatigue simulation analysis showed that the safety factor of the base-fixation titanium plate in the working state was 3.8 (>1.0), indicating that its fatigue performance met the application requirements. Compared with traditional buccal fixation, the novel base-fixation system has obvious advantages, suggesting its suitability as a new treatment method for clinical mandibular defect reconstruction.